Case Report: Left ventricular assist device implantation combined with cryoballoon ablation for ventricular tachycardia - Zhang, Shuang; Li, Jianming; Tan, Changming; Chen, Mingxian; Hu, Lin; Tang, Hanze; Liao, Liyi; Li, Xuping (Frontiers in Surgery, 2025)
We report a case of a patient with dilated cardiomyopathy who experienced recurrent ventricular tachycardia (VT) and multiple defibrillations following CRT-D implantation. Due to worsening cardiac function, the patient required surgical implantation of a left ventricular assist device (LVAD) as a bridge to heart transplantation. During the procedure, we used the Ensite three-dimensional mapping system to perform activation and substrate mapping of the VT targets, followed by endocardial and epicardial cryoballoon ablation of clinical VT. Subsequently, during LVAD implantation, dual cryoballoon ablation was applied around the surgical incision site to prevent VT associated with the surgical wound and the implanted device. At the 1-year follow-up, the patient had no recurrence of the original clinical VT and no new ventricular arrhythmias were observed.